Resolving Conflicts Between People and Over Time in the Transformation Toward Sustainability: A Framework of Interdependent Conflicts - Majer, Johann M.; Barth, Matthias; Zhang, Hong; van Treek, Marie; Trötschel, Roman (Frontiers in Psychology, 2021)
Transformative and mutually beneficial solutions require decision-makers to reconcile present- and future interests (i.e., intrapersonal conflicts over time) and to align them with those of other decision-makers (i.e., interpersonal conflicts between people). Despite the natural co-occurrence of intrapersonal and interpersonal conflicts in the transformation toward sustainability, both types of conflicts have been studied predominantly in isolation. In this conceptual article, we breathe new life into the traditional dialogue between individual decision-making- and negotiation research and address critical psychological barriers to the transformation toward sustainability. In particular, we argue that research on intrapersonal and interpersonal conflicts should be tightly integrated to provide a richer understanding of the interplay between these conflicts. We propose a novel, unifying framework of interdependent conflicts that systematically structures this interplay, and we analyze how complex interdependencies between the social (i.e., conflict between decision-makers) and temporal (i.e., conflict within a decision-maker) dimensions pose fundamental psychological barriers to mutually beneficial solutions. Since challenges to conflict resolution in the transformation toward sustainability emerge not only between individual decision-makers but also frequently between groups of decision-makers, we scale the framework up to the level of social groups and thereby provide an interdependent-conflicts perspective on the interplay between intra- and intergenerational conflicts. Overall, we propose simple, testable propositions, identify intervention approaches, and apply them to transition management. By analyzing the challenges faced by negotiating parties during interdependent conflicts and highlighting potential intervention approaches, we contribute to the transformation toward sustainability. Finally, we discuss implications of the framework and point to avenues for future research.